2013
DOI: 10.1007/s10695-013-9893-4
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet reduces local myostatin-1 paralog expression and alters skeletal muscle lipid content in rainbow trout, Oncorhynchus mykiss

Abstract: Muscle growth is an energetically demanding process that is reliant on intramuscular fatty acid depots in most fishes. The complex mechanisms regulating this growth and lipid metabolism are of great interest for human health and aquaculture applications. It is well established that the skeletal muscle chalone, myostatin, plays a role in lipid metabolism and adipogenesis in mammals; however, this function has not been fully assessed in fishes. We therefore examined the interaction between dietary lipid levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…Further, trends were observed in both myostatin-1a and -1b expression in response to the vehicle in both tissues, though not statistically significant. These data, along with our previous work showing changes in myostatin expression in response to a high-fat diet, provide evidence that myostatin may be responsive to lipid availability (Galt et al, 2013). …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Further, trends were observed in both myostatin-1a and -1b expression in response to the vehicle in both tissues, though not statistically significant. These data, along with our previous work showing changes in myostatin expression in response to a high-fat diet, provide evidence that myostatin may be responsive to lipid availability (Galt et al, 2013). …”
Section: Discussionsupporting
confidence: 77%
“…Samples were then centrifuged and plasma was isolated from packed cells. Glucose levels were analyzed in plasma (5 μL) using an Accu-Chek glucose meter (Roche) as previously described (Galt et al, 2013; Meyer et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that diet may affect the gene MSTN 1. In their study on Oncorhynchus mykiss (rainbow trout) with low (10%) and high (25%) lipid levels, Galt et al (2014) reported a significant decrease in gene expression in animals fed at high lipid rates. The authors underscored a possible relationship between lipid deposition and energy partition with a decrease in myostatin.…”
Section: Discussionmentioning
confidence: 99%
“…Diets with low and high fat were tested to determine MSTN expression in the rainbow trout fish (Oncorhynchus mykiss) by Galt et al (2014). They observed that a highfat diet reduces MSTN expression and alters skeletal muscle lipid content.…”
Section: Discussionmentioning
confidence: 99%